Mutations in Caenorhabditis briggsae identify new genes important for limiting the response to EGF signaling during vulval development. Issue 1 (January 2015) - Sharanya, Devika; Fillis, Cambree J.; Kim, Jaeyoung; Zitnik, Edward M.; Ward, Kelly A.; Gallagher, Molly E.; Chamberlin, Helen M.; Gupta, Bhagwati P.
SUMMARY Studies of vulval development in the nematode C. elegans have identified many genes that are involved in cell division and differentiation processes. Some of these encode components of conserved signal transduction pathways mediated by EGF, Notch, and Wnt. To understand how developmental mechanisms change during evolution, we are doing a comparative analysis of vulva formation in C. briggsae, a species that is closely related to C. elegans. Here, we report 14 mutations in 7 Multivulva (Muv) genes in C. briggsae that inhibit inappropriate division of vulval precursors. We have developed a new efficient and cost‐effective gene mapping method to localize Muv mutations to small genetic intervals on chromosomes, thus facilitating cloning and functional studies. We demonstrate the utility of our method by determining molecular identities of three of the Muv genes that include orthologs of Cel‐lin‐1 (ETS) and Cel‐lin‐31 (Winged‐Helix) of the EGF‐Ras pathway and Cel‐pry‐1 (Axin), of the Wnt pathway. The remaining four genes reside in regions that lack orthologs of known C. elegans Muv genes. Inhibitor studies demonstrate that the Muv phenotype of all four new genes is dependent on the activity of the EGF pathway kinase, MEK. One of these, Cbr‐lin(gu167), shows modest increase in the expression of Cbr‐lin‐3/EGF compared to wild type. These results argue that while Cbr‐lin(gu167) may act upstream of Cbr‐lin‐3/EGF, the other three genes influence the EGF pathway downstream or in parallel to Cbr‐lin‐3. Overall, our findings demonstrate that the genetic program underlying a conserved developmental process includes both conserved and divergent functional contributions.